Protein Tyrosine Phosphatases in Neuroblastoma: Emerging Roles as Biomarkers and Therapeutic Targets - Nunes-Xavier, Caroline E.; Zaldumbide, Laura; Mosteiro, Lorena; López-Almaraz, Ricardo; García de Andoin, Nagore; Aguirre, Pablo; Emaldi, Maite; Torices, Leire; López, José I.; Pulido, Rafael (Frontiers in Cell and Developmental Biology, 2021)
Neuroblastoma is a type of cancer intimately related with early development and differentiation of neuroendocrine cells, and constitutes one of the pediatric cancers with higher incidence and mortality. Protein tyrosine phosphatases (PTPs) are key regulators of cell growth and differentiation by their direct effect on tyrosine dephosphorylation of specific protein substrates, exerting major functions in the modulation of intracellular signaling during neuron development in response to external cues driving cell proliferation, survival, and differentiation. We review here the current knowledge on the role of PTPs in neuroblastoma cell growth, survival, and differentiation. The potential of PTPs as biomarkers and molecular targets for inhibition in neuroblastoma therapies is discussed.